1999
DOI: 10.1143/jjap.38.7122
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Properties of Interlayer Low Dielectric Polyimide during Cl-Based Plasma Etching of Aluminum

Abstract: Within the framework of the thermally activated process of the flux line or flux line bundles, and by time integration of the 1D equation of motion of the circulating current density J (ρ, t), which is suitable for thin superconducting films (R d, λ), we present numerical calculations of the current profiles, magnetization hysteresis loops and ac susceptibility χ n = χ n + iχ n for n = 1, 3 and 5 of a thin disc immersed in an axial time-dependent external magnetic field B a (t) = B dc + B ac cos(2πνt). Our cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, during the processing of CMOS/MEMS based devices polyimide will also go through the processing steps required for fabrication of the device. Plasma treatment and ion implantation are two examples of standard process steps which have been reported to modify the properties of polyimide films (6)(7)(8). These steps can affect properties of the film in different aspects and levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the processing of CMOS/MEMS based devices polyimide will also go through the processing steps required for fabrication of the device. Plasma treatment and ion implantation are two examples of standard process steps which have been reported to modify the properties of polyimide films (6)(7)(8). These steps can affect properties of the film in different aspects and levels.…”
Section: Introductionmentioning
confidence: 99%
“…Nakamura et al (10) have shown that oxygen plasma treatment would help to make the surface of polyimide film hydrophilic apart from increasing its adhesion strength to other films. Kim et al (7) have demonstrated that the dielectric constant of polyimide increases with exposure time to Cl plasma and decreases when exposed to SF 6 plasma. Eichhorn et al (11) have shown that ion implantation can modify or even destroy the chemical structure of polyimide films, depending on implantation dose and film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma etching has been a key means of Al patterning. [1][2][3][4][5] Reactive ion etching (RIE) suffers from such drawbacks as low plasma density and high plasma damage to the substrate. To circumvent these undesirable process characteristics, a magnetically enhanced RIE (MERIE) has been introduced 6 and applied to patterning Al thin films.…”
Section: Introductionmentioning
confidence: 99%